Magnetic confinement of diamagnetic objects for space utilization. (December 2018) - Wu, Zi-Qing; Liu, Ya-Li; Chen, Jing-Jie; Liu, Yong-Ming; Ahmad, Fiaz; Zeng, Xiang-Bin; Li, Jin; Shang, Peng; Yin, Da-Chuan
Abstract: Utilization of the space environment provides invaluable opportunities for researchers to fulfill challenging tasks that are impossible on Earth. Longtime sustainable containerless and simultaneously weightless condition is a desirable physical environment that can be easily obtained in outer space. However, in a space station, due to unpredictable disturbances, i.e., g-jitter, objects that are floating in containerless and weightless conditions may not be able to stay motionless at a specific location, making it difficult to conduct any investigation of the objects. In this study, we propose a method to confine objects without energy consumption using permanent magnets. Two types of confinement apparatuses made of permanent magnets were designed and manufactured. The apparatuses were used to demonstrate the capability of the magnetic field to confine diamagnetic objects without mechanical contact. We took confinement of a water droplet as an example and calculated the confinement performance of the two apparatuses. The results showed that the idea of using permanent magnets to confine diamagnetic objects without energy consumption in the space environment is feasible. Compared with other confinement methods, such as ultrasound and electrostatic confinement methods, the method proposed in this study is simple, efficient and inexpensive. Most importantly, the confined objects are restricted in a region with a low magnetic field. These advantages enable the method a potentially useful alternative for studying objects under containerless and weightless condition in space. Highlights: A new magnetic confinement method of diamagnetic objects for space utilization is proposed. Two types of confinement apparatuses were designed and manufactured. The confinement capability of apparatuses for diamagnetic objects is demonstrated.